Anticonvulsant effects of aerial parts of Passiflora incarnata extract in mice: involvement of benzodiazepine and opioid receptors - Shariati-Rad Schwann; Nassiri-Asl Marjan; Zamansoltani Farzaneh (BMC, 2007)
Abstract Background Passion flower (Passiflora incarnata) is used in traditional medicine of Europe and South America to treat anxiety, insomnia and seizure. Recently, it has shown antianxiety and sedative effects in human. Methods In this study, anticonvulsant effects of hydro- alcoholic extract of Passiflora, Pasipay, were examined by using pentylentetrazole model (PTZ) on mice. Pasipay, diazepam, and normal saline were injected intraperitoneally at the doses 0.4-0.05 mg/kg, 0.5-1 mg/kg and 10 ml/kg respectively 30 minutes before PTZ (90 mg/kg, i.p). The time taken before the onset of clonic convulsions, the duration of colonic convulsions, and the percentage of seizure and mortality protection were recorded. For investigating the mechanism of Pasipay, flumazenil (2 mg/kg, i.p) and naloxone (5 mg/kg, i.p) were also injected 5 minutes before Pasipay. Results An ED50 value of Pasipay in the PTZ model was 0.23 mg/kg (%95 CL: 0.156, 0.342). Pasipay at the dose of 0.4 mg/kg prolonged the onset time of seizure and decreased the duration of seizures compared to saline group (p < 0.001). At the dose of 0.4 mg/kg, seizure and mortality protection percent were 100%. Flumazenil and naloxone could suppress anticonvulsant effects of Pasipay. Conclusion It seems that Pasipay could be useful for treatment absence seizure and these effects may be related to effect of it on GABAergic and opioid systems. More studies are needed in order to investigate its exact mechanism.